EU-Funded Telemedicine Projects – Assessment of, and Lessons Learned From, in the Light of the SARS-CoV-2 Pandemic - Paleari, Laura; Malini, Virginia; Paoli, Gabriella; Scillieri, Stefano; Bighin, Claudia; Blobel, Bernd; Giacomini, Mauro (Frontiers in Medicine, 2022)
The Sars-Cov2 health emergency has demonstrated the need for developing structured telemedicine systems to protect citizens from the spread of the virus. Thereby, their importance and the nessecity to tailor their diffusion at large scale for providing services both at a distance and in time has been shown. For these reasons, the European Union advocates the digital transition of health systems for the next five years. The main aim of this work is to revisit the telemedicine research projects financed by European Community during the period 2000-2020 with particular respect to the results derived from their application. The analysis showed that some integration of tele-care and tele-health could be obtained with tele-monitoring systems and the implementation of Electronic Personal Record (EPR). Furthermore, telemedicine allows enhancing health care in critical environments, to protect health and life of the most vulnerable patients, and to encourage cross-border dialogue. The criteria of “from distance” and “timely delivered” are granted, but the effectiveness of the overall offered services highly depends on the availability and the quality of the input data. Unfortunately, this remains a relevant problem in the Sars-Cov2 pandemic.